Pengaruh Kemiskinan Terhadap Peningkatan Pertumbuhan Ekonomi Khususnya Inflasi dan Pengangguran di Kota Surabaya - Ismi Rosyidatul Ummah; Achmad Alfian Azizi; Muhammad Yasin (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The purpose of this research is to ascertain how poverty affects Surabaya's ability to develop economically. In this research, the degree of poverty, economic development, inflation, and unemployment in Surabaya are covered. The data used in this research are quantitative, or provided as numbers, making them first simpler to understand or compare. The data analysis approach in this research involves multiple linear regression to gather data and information, while SPSS22 is used to analyse the data. By employing software to verify the statistical significance of variables, data analysis was completed. The author additionally makes use of secondary data, data collection methods, and the documentation method while gathering and processing information from Surabaya City's Central Statistics Agency (BPS).